Effect of Acupressure Massage on Pregnant Women with Hyperemesis Gravidarum Trimester 1 - Octavia, Rina; Mardianti, Lina; Ashari, Elva Febri; Attamimi, Has'ad Rahman; Maesaraoh, Dianas (Jurnal Biologi Tropis, 2023)
Pregnancy experienced by women will certainly experience various changes that occur both physiologically and psychologically. This study aims to determine the effect of Acupressure massage on pregnant women with hyperemesis gravidarum in the first trimester at PMB Bd. Lilis Nurhasanah. This study was conducted quantitatively pre-experimentally. Data were analyzed in two ways, namely univariate and bivariate analysis, then hypothesis testing using the Wilcoxon test. The study found that respondents experienced more severe nausea and vomiting prior to receiving acupressure. However, respondents reported less nausea and vomiting after receiving acupressure. The impact of pressure point massage treatment on focuses LR3, SP6, and Li4 is powerful against hyperemesis in pregnant ladies in the wake of being given pressure point massage. The end is that giving pressure point massage rub affects diminishing queasiness and retching in pregnant ladies with hyperemesis gravidarum in the primary trimester.